Authoring augmented reality as situated multimedia - Sandor, Christian (Archīum Ateneo, 2014)
Augmented reality (AR) is an enabling technology for presenting information in relation to real objects or real environments. AR is situated multimedia or information that is positioned in authentic physical contexts. In this paper, we discuss how we address issues in creating AR content for educational settings. From the learning theory perspective, we explain that AR is a logical extension of multimedia learning theory. From the development perspective, we demonstrate how AR content can be created through our in situ authoring tool and our platform for handheld AR.